PENGARUH EKUIVALEN RATE BAGI HASIL, TINGKAT SUKU BUNGA DEPOSITO BPR DAN JUMLAH KANTOR BPRS TERHADAP JUMLAH NASABAH DEPOSITO iB MUDHARABAH PADA BPRS DI INDONESIA PERIODE 2016-2018 - Juliana Putri; Salman Alfarisi (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This study aims to determine the effect of the equivalent rate of profit sharing, interest rates on BPR deposits and the number of BPRS Offices on the number of mudharabah iB deposit customers at BPRS in Indonesia. The research method used is quantitative descriptive research using secondary data in the form of financial reports published by OJK in Sharia Banking Statistics (SPS) and Indonesian Banking Statistics (SPI) with time series data in the period of 2016-2018. The sample in this study all BPRS in Indonesia is 168 BPRS. Analysis of research using multiple linear regression analysis using application or supporting software namely PASW (Predictive Analytics SoftWare) Statistics 18, the results of research, it can be concluded that: 1) Equivalent rate of profit sharing (X1) has a significant negative effect of iB mudharabah deposit customers, 2) Variable interest rates on BPR deposits (X2) do not affect the number of mudharabah iB deposit customers. 3) The variable number of BPRS offices (X3) has a significant positive effect on the number of mudharabah iB deposit customers. 4) The coefficient of determination obtained is 0.586 or 58.6%. which means that 58.6% causes variable variable number of iB mudharabah (Y) deposit customers can be influenced by the equivalent rate of profit sharing, the level of BPR deposit rates and the number of BPRS offices, while the remaining 41.4% is influenced by other factors not included in the study.